Asian donor support for gender equality and women's empowerment: Comparative experience, challenges, and opportunities - Eugenia McGill (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
Since the 1990s, gender mainstreaming has been a widely accepted strategy for promoting gender equality within governments, multilateral agencies, and development NGOs, although critics continue to question its premises and results. This paper reviews how the development agencies of Australia, Japan, New Zealand, and the Republic of Korea, as well as the Asian Development Bank, have sought to promote gender equality through their activities, and considers lessons that can be drawn from their experience. The paper also considers the Philippines' harmonized guidelines on gender and development, and the experience of these development agencies in implementing the guidelines.
Keywords: F35; O2; 330; gender equality; gender mainstreaming; women's empowerment; donors; development agencies; Asia and Pacific